A lógica simbólica na medicina popular - Delgado Sobrinho, Antônio Talora [UNESP]; Ravagnani, Oswaldo Martins [UNESP]; Carvalho, Silvia M. S. [UNESP] (Universidade Estadual Paulista (Unesp), 1983)
Trabalho exploratório visando detectar a existência de uma lógica simbólica na medicina popular (fitoterapia).

The aim of this exploratiry paper is to detected the existence of a symbolic logic in folk medicine (phytotherapy).
The symbolic logic in the folk medicine
Keywords: Fitoterapia; Medicina popular; Curador; Plantas medicinais; Remédios e doenças; Representações simbólicas; Phytotherapy; Folk medicine; Folk healer; Medicinal plants; Medicines and illneses; Symbolic representations